SURVEY AND TEMPORAL AND EVOLUTIONARY ANALYSIS OF LINEAR WATER EROSION ON A SAMPLE HILLSLOPE OF THE LEOPOLDO RIVER - Francisco, M. R. [UNESP]; Oliveira, A. L. P. de [UNESP]; Furegatti, S. A. [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2023)
The article presents a temporal and evolutionary analysis of linear water erosion, as from a survey of a sample hillslope of the Leopoldo river, located in the municipality of Agudos (SP). The survey was elaborated from satellite images made available by Google Earth, which allowed to identify the main characteristics of erosive features. The analyzed characteristics are: slope position, length, width, line of inclination, shape, evolutionary stage, incision system, possible origin, curvature longitudinal and transversal. So, the article made it possible to study the erosions' behavior and the relationship with local morphology.
Keywords: soil erosion; gully; hillslope